2009
DOI: 10.1021/es802334e
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Size Effects on Uranium(VI) Adsorption to Hematite

Abstract: U(VI) adsorption on aerosol-synthesized hematite particles ranging in size from 12 to 125 nm was studied to explore nanoscale size effects on uranium adsorption. Adsorption on 70 nm aqueous-synthesized particles was also investigated to examine the effect of the synthesis method on reactivity. Equilibrium adsorption was measured over pH 3-11 at two U(VI) loadings. Surface complexation modeling, combined with adjustment of adsorption equilibrium constants to be independent of site density and surface area, prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 32 publications
4
83
1
Order By: Relevance
“…Sahu (2011) found that addition of copper dopant to TiO 2 structure increases the nanoparticle stability in suspension compared to pristine TiO 2 particles, and attributed this to charge imbalance created by replacement of Ti atoms by copper atoms. The modification in the properties of TiO 2 nanoparticles in the aqueous suspension influences the fate and transport in the environmental system, catalytic reactivity and contamination treatment efficiency (Gilbert et al, 2009;Gun'ko et al, 2001;Guzman et al, 2006;Mukherjee and Weaver, 2010;Waychunas et al, 2005;Zeng et al, 2009). Several studies have demonstrated effective bacterial inactivation potential of nano-sized TiO 2 suspensions for Escherichia-coli bacteria and found that concentration and size of the particles in the suspensions are very important parameters (Byrne et al, 2011;Liu and Yang, 2003;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sahu (2011) found that addition of copper dopant to TiO 2 structure increases the nanoparticle stability in suspension compared to pristine TiO 2 particles, and attributed this to charge imbalance created by replacement of Ti atoms by copper atoms. The modification in the properties of TiO 2 nanoparticles in the aqueous suspension influences the fate and transport in the environmental system, catalytic reactivity and contamination treatment efficiency (Gilbert et al, 2009;Gun'ko et al, 2001;Guzman et al, 2006;Mukherjee and Weaver, 2010;Waychunas et al, 2005;Zeng et al, 2009). Several studies have demonstrated effective bacterial inactivation potential of nano-sized TiO 2 suspensions for Escherichia-coli bacteria and found that concentration and size of the particles in the suspensions are very important parameters (Byrne et al, 2011;Liu and Yang, 2003;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, wildtype bacteriophages bind uranyl metal ions with a high absorption distribution coefficient Kd (Table 2, Figure S5). This is a much higher absorption rate in comparison to other nanomaterials [31][32][33]. The natural affinity of phage for U(VI) is so strong that the uranyl absorbed on the phage surface is proximity to the catalytic peptides, thus the absorption may facilitate uranyl reduction by Aβ-like peptides, although the tight binding is insufficient for catalysis.…”
Section: Batch Sorption Of U(vi) To Phagesmentioning
confidence: 99%
“…As shown in Figure 6, the sorption profiles of U onto these iron oxyhydroxides are generally similar and form S-type (or sigmoidal type) sorption edges at the pH range of 2-10. The sorption is very little or near zero at pH <3, the sorption increases dramatically with increasing pH, a near complete sorption of U is normally achieved at the pH 5 -6 and remains until pH 10 studied (Hsi and Langmuir 1985, Waite et al 1994, Payne et al 1998, Missana et al 2003, Tao et al 2004, Zeng et al 2009). In Figure 6, the sorption profiles of U onto synthetic and natural hematite are slightly different from those for ferric hydroxide and goethite.…”
Section: Uraniummentioning
confidence: 99%
“…In Figure 6, the sorption profiles of U onto synthetic and natural hematite are slightly different from those for ferric hydroxide and goethite. This difference is probably due to the limited surface area, particle sizes and thus the limited available sorption sites of the hemati te sorbents (Missana et al 2003, Zeng et al 2009). Ca and Mg at 10 -3 M do not significantly affect uranyl sorption (Hsi and Langmuir 1985), while the ion strength change of NaNO 3 from 0.1 M to 0.001 M appears to have little influence on the sorption prof iles of U onto iron oxides and hydroxides (Missana et al 2003).…”
Section: Uraniummentioning
confidence: 99%